Feasibility of measuring antigen–antibody interaction forces using a scanning force microscope - Stuart, J.K. (1999)
The molecular affinity scanning force microscopy (MASFM) described in this study was developed in an effort to test the possibility of antigen–antibody binding measurement using force-separation distance profiles. The MASFM configuration was comprised of a spherical glass bead as an MASFM probe, to which the fluorescein antigen has been covalently attached, and a silicon dioxide-based substrate, to which the antifluorescyl IgG antibody was covalently bound. The bead was glued to the tip of a commercial SFM cantilever. Adhesion forces have been measured between two different specific antigen–antibody pairs and between nonspecific surfaces bearing only glycidoxypropylsilane immobilization chemistry. In force-separation (F-s) measurements, nonspecific forces displayed relatively few force discontinuities and mean adhesion forces lower than those found for specific antigen–antibody measurements. Force-separation profiles measured between specific antigen–antibody pairs showed many discontinuities and had higher mean forces. Positive controls revealed that the mean forces were slightly reduced by the addition of free ligand. The magnitude of mean forces did not correlate with the respective activation enthalpies of the proteins, as would be expected. At lower force values the force histograms for the specific pairs and for positive controls were indistinguishable. None of the force-separation data sets could fit a Poisson discrete-force model. This statistical analysis showed a large relative contribution from nonspecific interactions. It is concluded that the use of the large sphere as an SFM probe is counterproductive: while the large sphere does sample a larger number of specific interactions during each measurement, it also samples at the same time a large proportion of nonspecific forces. The presence of the nonspecific force contributions is likely due to the deformation of the polymerized GPS spacer layer which is thought to be delaminated from the surface upon the application of tension across the specific antigen–antibody bonds.